A global architecture for broadband communication systems: the BERKOM approach - Popsecu-Zeletin, R.; Butscher, B.; Egloff, P.; Kanzow, J. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
The architecture and major solutions adopted for a global system based on a prototype broadband integrated services digital network, developed as part of the BERKOM pilot project 5 are outlined. A reference model has been developed for the global architecture in order to guarantee the coherent development of the different modules and their interworking in the global system. A description is given of the BERKOM test network and reference model of the enhanced services offered.< >